El impacto de la Guerra Civil española en la configuración de los museos. El caso del Museu d’Art de Girona - Gemma Domènech i Casadevall (Midas: Museus e Estudos Interdisciplinares)
Warfare and social revolutions are probably the greatest cause of heritage loss, and the Spanish Civil War (1936-1939) was no exception. Along with the destruction, there was an enormous work of protection led by the government of the Republic, and the Catalan government in Catalonia, which guaranteed the safeguarding of a large part of the heritage. Some of these historical-artistic assets came under the jurisdiction of a new body, the National Artistic Heritage Protection Service (SDPAN), at the end of the war. In this article, we propose to address the impact that the policies carried out during and at the end of the military conflict have had on the configuration of Catalan museums. This work is framed in the IGUEMUS project, “The impact of the Civil War on shaping museums in Catalonia. The traceability, location, and destination of saved cultural assets” (2022-2026). It was funded by the Spanish Ministry of Science and Innovation and the European Regional Development Agency and Fund (PID 2021-124518NB-I00). Beyond presenting the project and highlighting the opportunity that it represents for the history of museology, we discuss the first findings from the Museu d’Art de Girona case study. In this case, we can establish how a substantial part of the collection entered in the summer of 1936, as a result of Republican policies to protect religious heritage, and how, at the end of the war, it was not returned to the parishes of origin by decision of those responsible for the SDPAN, giving rise to the current configuration of the Museu d'Art de Girona.